I like My Voice Better: Self-Enhancement Bias in Perceptions of Voice Attractiveness. (September 2013) - Hughes, Susan M; Harrison, Marissa A
Previous research shows that the human voice can communicate a wealth of nonsemantic information; preferences for voices can predict health, fertility, and genetic quality of the speaker, and people often use voice attractiveness, in particular, to make these assessments of others. But it is not known what we think of the attractiveness of our own voices as others hear them. In this study eighty men and women rated the attractiveness of an array of voice recordings of different individuals and were not told that their own recorded voices were included in the presentation. Results showed that participants rated their own voices as sounding more attractive than others had rated their voices, and participants also rated their own voices as sounding more attractive than they had rated the voices of others. These findings suggest that people may engage in vocal implicit egotism, a form of self-enhancement.